The Effectiveness of Using the TGT Learning Model in Improving Kalam Proficiency: English - Suci Rahma Danti Lubis; Fachru Razi; Didin Syamsudin (Universitas Djuanda, 2026)
This study aims to examine the effectiveness of the Teams Games Tournament (TGT) learning model in enhancing maharah kalam, or Arabic speaking skills. The research is conducted qualitatively through a literature review of various relevant sources, including books, scientific articles, and previous research reports. TGT is a cooperative learning approach that integrates group work with game elements and tournaments to increase student motivation and participation. The TGT model is part of a cooperative learning approach that combines group work with game and tournament elements to increase student motivation and participation. Based on the literature review, the TGT model is considered effective in creating an engaging, competitive, and collaborative learning environment, which significantly stimulates the development of students' Arabic speaking abilities. Group discussions allow students to actively use Arabic in communicative contexts, while the game and tournament elements foster emotional and cognitive engagement. Furthermore, the TGT approach promotes intensive interpersonal interaction, enriches vocabulary, and boosts students' confidence in speaking.